Succeeding through Uncertainty: Three L2 Students in a First-Year Composition Class - Stuart, Christian D. D. (My University, 2012)
This qualitative study examines the unique challenges of multilingual students (referred to in the study as "L2 students") in a first-year writing class at a large public U.S. university. Following a case-study approach, the experiences of three L2 students, three native English-speaking students (referred to in the study as "L1 students"), and their instructor, all in the same first-year writing class, were observed. Data for the study consisted of classroom observations, multiple interviews with each participant, and student writing samples that were collected throughout the quarter. These data were then analyzed through a grounded theory approach using the computer software program ATLAS.ti, and the student writing samples were examined through the scope of intertextual analysis. Analysis of the data revealed that the L2 and the L1 students were surprisingly similar in their initial approach to the class: Students in both groups were clear in their early interviews that they had enrolled in the class only because it was a requirement, and they did not think the class would be relevant to their academic goals and interests. However, in the process of actually taking the class, the L1 students viewed it as familiar and predictable, while the L2 students expressed feelings of uncertainty and anxiety. For the group of L2 students, these feelings of uncertainty and anxiety prompted them to actively participate in the class, while the L1 students, in relying on a sense of familiarity in the class, were content in only minimally participating in the class. Despite this emergent difference between the L2 and the L1 students, both groups of students found institutional success in the course in that each participant earned an above-passing grade and the subsequent core credit. At the same time, only the L2 students expressed an actual sense of learning in taking the class, indicating a significant change from their initial thinking that the class was irrelevant to a new belief that the class had in fact contributed to perceptible, relevant academic literacy development.
Thesis (Ph.D.)--University of Washington, 2012
Keywords: Academic Literacy Development; First-Year Composition; L2 Students; Qualitative Study; English as a second language; Rhetoric; Teacher education; English